2016
DOI: 10.1371/journal.ppat.1005966
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Dictates Protein Kinase R Susceptibility to Unrelated Viral Antagonists

Abstract: During millions of years of coevolution with their hosts, cytomegaloviruses (CMVs) have succeeded in adapting to overcome host-specific immune defenses, including the protein kinase R (PKR) pathway. Consequently, these adaptations may also contribute to the inability of CMVs to cross species barriers. Here, we provide evidence that the evolutionary arms race between the antiviral factor PKR and its CMV antagonist TRS1 has led to extensive differences in the species-specificity of primate CMV TRS1 proteins. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…The effects of differential PKR inhibition have so far been addressed in yeast assays and cultured cells, in which yeast growth, eIF2␣, and PKR phosphorylation, mRNA translation, or virus replication have been used as readouts for PKR inhibition. [9][10][11]19,41 Currently, we have very limited information about the effects of differential PKR inhibition from in vivo infection models. It seems clear that no or ineffective PKR inhibition would result in abortive infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of differential PKR inhibition have so far been addressed in yeast assays and cultured cells, in which yeast growth, eIF2␣, and PKR phosphorylation, mRNA translation, or virus replication have been used as readouts for PKR inhibition. [9][10][11]19,41 Currently, we have very limited information about the effects of differential PKR inhibition from in vivo infection models. It seems clear that no or ineffective PKR inhibition would result in abortive infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that positively selected amino acid residues contribute directly to PKR sensitivity to inhibitors from poxviruses and herpesviruses. [9][10][11] Most poxviruses encode two PKR inhibitors, which are called K3 (encoded by K3L) and E3 (encoded by E3L) in VACV, the prototypic poxvirus. 3 K3 is an eIF2␣ homolog and is thought to act as a pseudosubstrate inhibitor by binding to activated, phosphorylated PKR to prevent its interaction with eIF2␣.…”
Section: Introductionmentioning
confidence: 99%
“…Human CMV TRS1 only inhibited human PKR but not PKR from old world monkeys while the TRS1 ortholog from African green monkey CMV inhibited AGM but not human PKR. Intriguingly, mutation of a single amino acid in human PKR (position 489), which determines susceptibility to human or AGM TRS1, is also involved in the weak sensitivity of human PKR to VACV K3 inhibition, highlighting that inhibitors from different pathogens can be affected by mutations in important antiviral proteins [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…HeLa (human, ATCC #CCL-2), HeLa PKR-knock-down( kd ), kindly provided by Dr. Charles Samuel [44], HeLa PKR-knock-out, kindly provided by Dr. Adam Geballe [10], RK13+E3L+K3L cells (rabbit) [45], tert-GF (tert immortalized gibbon fibroblasts, kindly supplemented with 5% fetal bovine serum or 10% horse serum (BT cells) and 100 IU/ml penicillin/streptomycin (Gibco). HeLa PKR kd cells were maintained in medium containing 1 µg/ml puromycin (Sigma).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation